Copper foil for negative electrode collector of lithium ion secondary battery

By adjusting the residual stress difference and yield strength between the roller surface and the deposition surface of the electrolytic copper foil, and optimizing the void volume, the problem of copper foil being easily damaged under high circulation in lithium-ion secondary batteries is solved, and high capacity is achieved , the excellent cycle characteristics and long life of lightweight batteries.

CN116706083BActive Publication Date: 2024-12-20CHANG CHUN PETROCHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310393051.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-03
Filing Date
2020-01-15
Publication Date
2024-12-20
Estimated Expiration
2040-01-15

AI Technical Summary

Technical Problem

The copper foil of the existing lithium-ion secondary battery is prone to wrinkle, tear, and cracking under high charge and discharge cycles, and the expansion and contraction of the negative electrode active material leads to poor circulation characteristics, affecting battery life.

Method used

Using electrolytic copper foil with controlled characteristics, the residual stress difference and yield strength between its roller surface and the deposited surface are adjusted to reduce the risk of wrinkling and cracking, and the void volume is optimized to improve adhesion and durability.

Benefits of technology

The high-capacity and lightweight design of lithium-ion secondary batteries is achieved, which extends the charging-discharge cycle life, avoids cracking and rupture of copper foil during cycle testing, and improves the adhesion characteristics of the active material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116706083B_ABST
    Figure CN116706083B_ABST
Patent Text Reader

Abstract

An electrolytic copper foil having properties suitable for use as a negative electrode collector of a lithium ion secondary battery. The copper foil has a thickness of 11 to 45 kg / mm 2 The yield strength is within the range, and the residual stress difference between the roller surface and the deposition surface is at most 95 MPa. The present disclosure also describes a negative electrode collector for a lithium ion secondary battery, a lithium ion secondary battery including a negative electrode, and a battery containing the negative electrode collector.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with application number 202010044774.X, application date January 15, 2020, and invention name “Copper foil for negative electrode collector of lithium-ion secondary battery”. Technical Field

[0002] The present invention relates to an electrolytic copper foil with high durability and processability and also relates to a lithium ion secondary battery prepared using the electrolytic copper foil. Background Art

[0003] Lithium-ion secondary batteries have a combination of high energy and high power density, making them a technology of choice for portable electronic devices, power tools, electric vehicles (EVs), energy storage systems (ESS), mobile phones, tablets, aerospace applications, military applications, and railways, where electric vehicles (EVs) include hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and pure battery electric vehicles (BEVs). If electric vehicles (EVs) replace most of the transportation powered by fossil fuels (e.g., gasoline, diesel fuel, etc.), lithium-ion secondary batteries will significantly reduce greenhouse gas emissions. The high energy efficiency of lithium-ion secondary batteries can also allow them to be used in various power grid applications, including improving the quality of energy collected from wind, solar, geothermal and other renewable energy sources, thereby contributing to their wider use in building a sustainable energy economy.

[0004] Therefore, lithium ion secondary batteries have aroused strong interest in basic research of commercial capital and government and academic laboratories. Although there have been many research and development in this field in recent years, and lithium ion secondary batteries are currently in use, there is still a need to improve the battery with higher capacity, higher current, and more charge / discharge cycles to extend its usable life. In addition, it is necessary to improve the weight of the battery to improve the application in various environments such as vehicles, portable electronic devices and aerospace.

[0005] Lithium-ion secondary batteries usually include a negative electrode collector of a metal foil coated with a negative electrode active material. Because copper is a good current conductor, copper foil is often used as a negative electrode collector. As the demand for reducing battery weight becomes more and more urgent, thinner collectors are needed to reduce the size and weight of lithium-ion secondary batteries. Such thinner collectors are prone to wrinkling, tearing, cracking, and other forms of damage. In addition, in order to increase the capacity of lithium-ion secondary batteries, materials such as silicon (Si), germanium (Ge), and tin (Sn) are mixed or filled in the battery with high-capacity active materials, which will aggravate the expansion and contraction of the active material and increase the stress of the copper foil in contact with the active material. Furthermore, in some recent developments, in order to increase the capacity of the battery, the copper foil used as the electrode is folded and wound. If the copper foil cannot withstand the expansion and contraction of the active material during the use of the battery and the folding and winding of the copper foil during the production of the battery, it will have an adverse effect on the cycle characteristics of the battery.

[0006] Therefore, there is still a need for improved copper foil for lithium ion secondary batteries. This includes the need for thinner copper foil with improved processability and durability, and when the copper foil is combined with a negative electrode active material to provide a lithium ion secondary battery, it will not fail under high charge and discharge cycles due to separation between the copper foil and the negative electrode active material or fracture of the copper foil. The required thinner copper foil must meet the goals of reducing the weight of the lithium ion secondary battery and increasing the capacity of the lithium ion secondary battery. Summary of the invention

[0007] In general, the invention described herein relates to a copper foil, such as an electrolytic copper foil that can be used as a negative electrode collector in a lithium ion secondary battery. The copper foil prepared has controlled properties, such as a controlled yield strength and a controlled difference between the residual stress on the deposited surface and the roller surface of the copper foil. The copper foil has excellent processability, low wrinkling and cracking.

[0008] In a first aspect, the present invention includes an electrolytic copper foil, comprising a roller surface and a deposition surface opposite to the roller surface. The roller surface and the deposition surface of the electrolytic copper foil each have residual stress, wherein the residual stress difference between the roller surface and the deposition surface of the electrolytic copper foil is at most 95 MPa.

[0009] In addition, the yield strength of the electrolytic copper foil is 11kg / mm 2 Up to 45kg / mm 2 , for example, about 16 kg / mm 2 To about 36kg / mm 2 within the range.

[0010] Optionally, the residual stress difference between the roller surface and the deposition surface of the electrolytic copper foil is at most 85 MPa, for example, at most 81 MPa.

[0011] Optionally, the residual stress difference between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 MPa to 95 MPa, for example, in the range of 7.4 MPa to 85 MPa, or in the range of 7.4 MPa to 81 MPa.

[0012] Optionally, the void volume (Vv) value of the deposition surface of the electrolytic copper foil is about 0.15 (μm 3 / μm 2 ) to about 1.30(μm 3 / μm 2 ), for example, about 0.18 (μm 3 / μm 2 ) to about 1.11(μm 3 / μm 2 ), or about 0.25 (μm 3 / μm 2 ) to about 1.00(μm 3 / μm 2 ).

[0013] Optionally, the electrolytic copper foil has a thickness of about 3 μm to about 20 μm.

[0014] In some cases, the residual stress of the deposited surface of the electrolytic copper foil is in a range of -40 MPa to 100 MPa.

[0015] In some other cases, the residual stress of the roller surface of the electrolytic copper foil is in a range of -47 MPa to 42 MPa.

[0016] Optionally, the core void volume (Vvc) value of the deposited surface of the electrolytic copper foil is 0.14 (μm 3 / μm 2 ) to about 1.15 (μm 3 / μm 2 ).

[0017] Optionally, the dale void volume (Vvv) value of the deposition surface of the electrolytic copper foil is at most 0.15 (μm 3 / μm 2 ).

[0018] In a second aspect, the present invention includes a negative electrode current collector comprising the electrolytic copper foil according to the first aspect of the present invention.

[0019] In a third aspect, the present invention includes a negative electrode, comprising the negative electrode current collector of the second aspect of the present invention, and further comprising a negative electrode active material coated on the negative electrode current collector.

[0020] In a fourth aspect, the present invention comprises a lithium ion secondary battery comprising the negative electrode according to the third aspect of the present invention.

[0021] Optionally, the lithium ion secondary battery has a charge-discharge cycle life of at least 900 times.

[0022] In a fifth aspect, the present invention comprises a device comprising a lithium ion secondary battery according to the fourth aspect of the present invention.

[0023] The electrolytic copper foils described herein exhibit excellent properties when used in lithium-ion secondary batteries. In addition to being able to manufacture lightweight lithium-ion secondary batteries with high capacity, such lithium-ion secondary batteries prepared from these electrolytic copper foils have excellent cycle characteristics. For example, the copper foils will not crack, wrinkle, or even break during or before the charge-discharge cycle test. In addition, the electrolytic copper foils have excellent adhesion properties to active materials (e.g., carbon materials) used in the battery.

[0024] The above summary of the invention is not intended to represent all embodiments or all aspects of the present disclosure. Instead, the above summary of the invention only provides examples of the novel aspects and features described herein. The above features and advantages and other features and advantages of the present disclosure will be apparent from the following detailed description of representative embodiments and modes for implementing the present invention when combined with the accompanying drawings and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present disclosure will be better understood through the following description of exemplary embodiments and with reference to the accompanying drawings.

[0026] Figure 1 Displays a stress-strain diagram for a material such as mild steel.

[0027] Figure 2 Displays stress-strain diagrams for materials such as high-strength steel or stainless steel.

[0028] Figure 3 Displays a stress-strain diagram for a low-strength metal such as thin copper foil.

[0029] Figure 4 Displays a stress-strain diagram illustrating the Extension Under Load method used to quantify yield strength.

[0030] Figure 5 Displays 3D surface plots and material ratio plots.

[0031] Figure 6 Displays the details of the load factor graph.

[0032] The present disclosure is open to various modifications and alternative forms. Some representative embodiments are shown by way of example in the drawings and will be described in detail herein. However, it should be understood that the present invention is not limited to the specific form disclosed. On the contrary, the present disclosure encompasses all modifications, equivalents and alternatives that fall within the spirit and scope defined by the claims of the present invention.

[0033] Explanation of symbols

[0034] 110, 210, 412 curves

[0035] 112 points

[0036] 410 vertical coordinate line

[0037] 414 Yield strength at 0.5% full strain

[0038] 510 Peak

[0039] 512 Valley

[0040] Areas 514, 610, 612, 614, 616

[0041] A-A' tangent

[0042] B-B' straight line

[0043] C, Z point

[0044] EF line. DETAILED DESCRIPTION

[0045] The articles manufactured herein relate to an electrolytic copper foil having quantifiable properties and providing good performance as a current collector. For example, these electrolytic copper foils can be combined with active materials to provide a negative electrode for a lithium-ion secondary battery. In some embodiments, the electrolytic copper foil has a low residual stress difference between the roller surface and the deposition surface and a yield strength that balances strength requirements while avoiding brittleness. In some other embodiments, the electrolytic copper foil is characterized by adjusting the void volume of the copper foil to a specific amount.

[0046] As used herein, the "roller surface" of the electrolytic copper foil refers to the surface of the electrolytic copper foil that contacts the cathode roller during the electrodeposition process, and the "deposition surface" refers to the opposite side of the roller surface, or the surface of the electrolytic copper foil that contacts the electrolyte during the electrodeposition process of forming the electrolytic copper foil. These terms relate to a manufacturing method for producing an electrolytic copper foil, which includes partially immersing a rotating cathode roller assembly in an electrolyte containing copper ions. Therefore, under the action of the electric current, the copper ions are attracted to the cathode roller and reduced, resulting in copper metal plating on the surface of the cathode roller, and thereby forming an electrolytic copper foil on the surface of the cathode roller. By rotating the cathode roller and removing the electrolytic copper foil as the formed copper foil rotates out of the electrolyte with the rotating cathode roller, the electrolytic copper foil is formed and removed from the cathode roller in a continuous process. For example, the electrolytic copper foil can be pulled out when it is formed on the cathode roller and traverse or pass through the roller in a continuous process.

[0047] As used herein, "residual stress" is the stress that exists in an object, component, or structure after all external applied forces have been removed. When the residual stress is compressive stress, its value is indicated by a minus sign ("-") before the value. When the residual stress is tensile stress, a positive sign ("+") is used before the value.

[0048] In some embodiments, by minimizing the residual stress difference (ΔRS) between the roller surface and the deposition surface of the electrolytic copper foil, the cycle life of the battery including the electrolytic copper foil is extended. That is, the battery using the electrolytic copper foil with a larger ΔRS has a shorter service life than the battery using the electrolytic copper foil with a smaller ΔRS. Therefore, in some embodiments, the ΔRS is minimized (e.g., less than about 95 MPa, less than about 85 MPa, or less than about 81 MPa).

[0049] If the ΔRS of the electrolytic copper foil is too large (e.g., greater than 95 MPa), it may be more easily damaged than an electrolytic copper foil that maintains a low residual stress (e.g., less than about 95 MPa). Therefore, if the ΔRS of the electrolytic copper foil is too high, the electrolytic copper foil will fail due to excessive shrinkage and expansion during battery cycling, which will have a negative impact on battery performance. Therefore, if the ΔRS of the electrolytic copper foil is too large, the cycle life of the battery is poor, and the electrolytic copper foil is easily broken due to excessive expansion and contraction during the cycle life test.

[0050] In some embodiments, the ΔRS between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 MPa to 95 MPa. In some embodiments, the ΔRS between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 MPa to 85 MPa. In some embodiments, the ΔRS between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 MPa to 81 MPa.

[0051] As used herein, "yield strength" is a material property defined as the stress at which a material begins to deform plastically. Generally, yield strength is determined by measuring the strain under applied stress and analyzing the data (e.g., by a stress-strain diagram). Because the shape of the curve in a stress-strain diagram can vary greatly depending on the properties of the material being tested, different methods can be used to measure and determine the yield strength in a stress-strain diagram, depending on the material.

[0052] Figure 1 A stress-strain diagram is shown for a material such as mild steel. These materials exhibit a characteristic dip at the end of the elastic (or mostly elastic) region of the stress-strain curve 110. Thus, such materials show a particular characteristic point 112. The stress at point 112 is referred to as the "yield point" or "upper yield point."

[0053] Figure 2 A stress-strain diagram is shown for a material such as high strength steel or stainless steel. These materials do not show a specific yield point, but instead produce a smooth curve 210 with a linear initial portion, as shown by the tangent line A-A' in the figure. In this case, the stress required to produce an offset of 0.2% can be used as a standard strength equivalent to the yield point. That is, the yield strength at an offset of 0.2%, referred to as the "0.2% offset yield strength", is obtained by drawing a straight line BB' parallel to the tangent line A-A' of the linear portion at a 0.2% offset from the tangent line A-A', which intersects the X-axis at a strain equal to 0.002, and measuring the yield strength at the point C where the straight line BB' intersects the curve 210. Therefore, the 0.2% offset yield strength is the stress read at point C of the curve 210.

[0054] For some materials, such as low-strength metals (e.g., thin copper foil), these materials have a nonlinear stress-strain relationship, making it difficult to accurately measure plastic strain. Figure 3 Shows the stress-strain curve for a low-strength metal. The featureless smooth curvature depicted in the figure illustrates the difficulty in accurately measuring plastic strain. In other words, the difficulty lies in the fact that there is no yield point in the curve, and because the curve has no clear initial linear portion, it is difficult to calculate the 0.2% offset yield strength.

[0055] Therefore, for low-strength materials, such as electrolytic copper foil, you can use Figure 4 The method is shown in FIG. 4 . The method requires drawing a vertical coordinate line 410 (line EF) on the stress-strain diagram, which intersects the curve 412 at a point on the x-axis where the elongation at that point is equal to a specific elongation. The stress value at point Z at the intersection of line EF is defined as the "yield strength at 0.5% full strain" or "0.5% EUL", which is represented by 414 in the figure. In some embodiments, the yield strength is the yield strength of 0.5% EUL.

[0056] If the yield strength of the electrolytic copper foil is too high, for example, higher than about 45 kg / mm 2 , the electrolytic copper foil is brittle (e.g., low toughness) and is more likely to crack and break. For example, when the yield strength of the electrolytic copper foil is too high, a battery made using the electrolytic copper foil may fail due to cracking or breaking during cycling. In contrast, when the yield strength of the electrolytic copper foil is too low, for example, less than about 11 kg / mm 2 , the electrolytic copper foil is easy to bend and wrinkle, and the battery cycle characteristics it provides are also poor.

[0057] The yield strength of the electrolytic copper foil and the residual stress on the roller surface and the deposition surface can be adjusted by a variety of methods. For example, the residual stress on the roller surface can be adjusted by mechanical or chemical grinding of the cathode roller surface. The yield strength and the residual stress on both sides of the electrolytic copper foil can also be adjusted by changing the conditions of electrodeposition, for example, changing the pulse current electroplating or pulse reverse current electroplating method used. The yield strength and residual stress difference of the copper foil can also be adjusted by adding organic additives to the electroplating solution, for example, 3-(benzothiazol-2-ylthio) propane sulfonate (ZPS), 3-(1-pyridyl) propane sulfonate (PPS), 2-aminobenzenesulfonic acid, 5-amino-2-chlorobenzenesulfonic acid, 1,1-dioxo-1,2-benzothiazol-3-one (saccharin), animal glue, gelatin, polyethylene glycol, polypropylene glycol, starch, carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), polyethylene imine (PEI), polyacrylamide and combinations thereof. In some embodiments, the concentrations of polyethylene imine and saccharin in the electroplating solution can be adjusted to control the properties of the electrolytic copper foil.

[0058] Figure 5 Displays the 3D surface and the derivation of the loading rate map used to obtain the volume parameters. Figure 5 The left side of FIG. 1 is a three-dimensional illustration representing the surface geometry of a surface (eg, a roller surface or a deposition surface of an electrolytic copper foil). Figure 5 The right side of FIG. 1 shows the derivation of the loading rate curve obtained by ISO standard method ISO 25178-2:2012, which spans 0% loading rate (material ratio, mr) at the top of the highest peak 510 to the bottom of the lowest valley 512 at 100% loading rate. The void volume (Vv) is calculated by integrating the volume of the voids enclosed above the surface and below the horizontal cutting plane at the height corresponding to a specific loading rate (mr) between 0% (top of peak 510) and 100% (bottom of valley 512). For example, the void volume at a loading rate of 70% is as follows Figure 5 This is shown as the shaded area 514 in the right figure.

[0059] Figure 6 More details of the loading ratio graph and some of the relationships defined for various volume parameters are shown. The core void volume (Vvc) is the difference in void volume between two loading ratios, such as the difference in void volume between mr1 and mr2 shown in area 610. For example, a core void volume can be selected where mr1 is 10% and mr2 is 80%. The trough void volume (Vvv), also known as the valley void volume, is the void volume for a specific mr value, such as the void volume where mr is 80% as shown in area 612. The void volume (Vv) at mr1 is the sum of the core void volume (Vvc) between mr1 and mr2 (area 610) and the trough void volume (Vvv) at mr2 (area 612). Other areas include the peak material volume (peak material volume, Vmp) (area 614) and the core material volume (core material ratio, Vmc) (area 616).

[0060] In some embodiments, the electrolytic copper foil has a controlled range of void volume between a low value and a high value, for example, between about 0.15 (μm 3 / μm 2 ) and about 1.30 (μm 3 / μm 2 When the void volume is too small, for example, less than about 0.15 (μm 3 / μm 2 ), due to the weak anchor effect, the adhesion of the electrolytic copper foil to the active material is poor. In other words, since the material cannot be smoothly anchored to the surface, its adhesion is poor. On the contrary, if the void volume is too large, for example, higher than about 1.30 (μm 3 / μm 2 ), the active material cannot be evenly coated on the surface of the electrolytic copper foil. In other words, a large void volume corresponds to large voids on the surface of the electrolytic copper foil, and the active material cannot effectively fill all the voids, leaving some uncovered or covered voids between the electrolytic copper foil and the active material layer. Therefore, in both too low and too high regions, the adhesion of the electrolytic copper foil to the active material is poor, and the battery prepared from the electrolytic copper foil whose void volume is not within the controlled range has poor battery characteristics.

[0061] For the deposition surface and roller surface of electrolytic copper foil, the void volume value is 0.15 to 1.30 (μm 3 / μm 2), and are independently selected between the deposition surface and the roller surface. It should be clearly understood that these ranges are continuous and can be expressed as: 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65 0, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70 , 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29 or 1.30 (μm) 3 / μm 2 ), each value represents the endpoint of a range of values. In some embodiments, the void volume of the deposition surface is between 0.18 and 1.11 (μm 3 / μm 2 In some embodiments, the void volume of the deposition surface is in the range of 0.25 to 1.00 (μm 3 / μm 2 ) range.

[0062] In some embodiments, the core void volume (Vvc) of the deposited surface of the electrolytic copper foil is between 0.14 and 1.15 (μm 3 / μm 2 ) range.

[0063] In some embodiments, the void volume (Vvv) of the valley portion of the deposited surface of the electrolytic copper foil is at most 0.15 (μm 3 / μm 2).

[0064] In some embodiments, the core void volume (Vvc) of the roll surface of the electrolytic copper foil is within a range of 0.14 to 1.15 (μm 3 / μm 2 ) range.

[0065] In some embodiments, the void volume (Vvv) of the trough portion of the roller surface of the electrolytic copper foil is at most 0.15 (μm 3 / μm 2 ).

[0066] As used herein, "rust-proof coating" refers to a coating applied to a metal that prevents degradation of the coated metal, for example due to corrosion. In some embodiments, the electrolytic copper foil includes a rust-proof coating formed on its surface. The rust-proof coating may be prepared by any known method, including immersing the formed electrolytic sheet or passing it through a solution containing a rust-proof forming additive. For example, a plating bath containing any one or more of zinc (Zn), chromium (Cr), nickel (Ni), cobalt (Co), molybdenum (Mo), vanadium (V) and combinations thereof; or an organic compound that forms a rust-proof layer, such as an azole compound. This process may be continuous and part of the overall process for preparing the electrolytic copper foil.

[0067] Charge-discharge testing refers to a test in which a voltage is applied to the positive and negative electrodes of a battery to charge the battery, and then the positive and negative electrodes are connected to a load and a current is passed through the load to discharge the battery. Charging and discharging represent a charge-discharge cycle. This test can be used to simulate the performance of a battery in repeated use (e.g., repeated charging and discharging) and the related service life. "Cycle life" and "charge-discharge cycle life" are defined as the number of charge-discharge cycles a battery can perform before its nominal capacity is less than 80% of its initial rated capacity.

[0068] In some embodiments, the electrolytic copper foil can be used as a collector of a battery (e.g., a lithium-ion secondary battery) and in a device. The device used herein includes any item or component that requires electricity for its operation. For example, independent, isolated and mobile components and devices that require small and light batteries. These devices may include, but are not limited to, vehicles (e.g., cars, trams, buses, trucks, ships, submarines, airplanes), computers (e.g., as microcontrollers, notebooks, tablet computers), phones (e.g., smart phones, wireless phones), personal health monitoring and maintenance equipment (e.g., blood glucose monitors, pacemakers), tools (e.g., electric drills, electric saws), lighting devices (e.g., flashlights, emergency lighting, signs), handheld measuring devices (e.g., pH meters, air monitoring devices) and residential units (e.g., in spacecraft, trailers, houses, airplanes, submarines).

[0069] It should be understood that within the scope of the present disclosure, the technical features mentioned above and below (such as embodiments) can be freely combined with each other to form new or better technical solutions, which are omitted for the sake of brevity.

[0070] Example

[0071] 1. Preparation of electrolytic copper foil

[0072] Copper wire was dissolved in a 50 wt% aqueous sulfuric acid solution to prepare a copper sulfate electrolyte containing 320 g / L copper sulfate (CuSO4·5H2O) and 80 g / L sulfuric acid. Hydrochloric acid (obtained from RCI Labscan) was added to provide a chloride ion concentration of 30 mg / L in the copper sulfate electrolyte. Additional ingredients were added per liter of copper sulfate electrolyte, including 4.0 mg to 14.5 mg of PEI (polyethyleneimine, linear, Mn=5000, purchased from Sigma-Aldrich) and 2.3 mg to 8.3 mg of saccharin (1,1-dioxo-1,2-benzothiazol-3-one, purchased from Sigma-Aldrich) to provide a variety of different electrolytes.

[0073] The system for manufacturing electrolytic copper foil includes a metal cathode roller and an insoluble metal anode. The metal cathode roller is rotatable and has a polished surface. In the system, the insoluble metal anode is arranged at approximately the lower half of the metal cathode roller and surrounds the metal cathode roller. Continuous electrodeposition is used to manufacture electrolytic copper foil, which is made by flowing a copper sulfate electrolyte between the metal cathode roller and the insoluble metal anode, applying an electric current between the two so that copper ions are attracted to the metal cathode roller and reduced, which causes copper to be electrodeposited on the metal cathode roller to form an electrolytic copper foil. When a predetermined thickness is obtained, the electrolytic copper foil is separated from the metal cathode roller. The deposition conditions are that the liquid temperature of the copper sulfate electrolyte is about 45°C and the current density is about 40A / dm2. The thickness of the prepared electrolytic copper foil is about 6μm.

[0074] After the electrolytic copper foil is prepared, its surface is treated with an anti-rust material, for example, in a chromium electroplating bath, the electrolytic copper foil is passed through the electroplating bath in a continuous manner by a guide roller. The anti-rust treatment is carried out in an electroplating bath containing 1.5g of chromium trioxide (CrO3, purchased from Sigma-Aldrich) per liter, at a liquid temperature of 25°C and a current density of about 0.5A / dm 2 This is done for about 2 seconds.

[0075] The electrolytic copper foil is passed through an air knife to remove any excess coating and to dry the electrolytic copper foil at the end of the process and before being wound into a roll. The roll of electrolytic copper foil can then be stored and used for further processing, such as for the manufacture of lithium-ion secondary batteries.

[0076] 2. Laminated lithium-ion secondary battery

[0077] The stacked lithium-ion batteries were prepared as follows and subjected to high rate charge / discharge tests.

[0078] N-methyl-2-pyrrolidone (NMP) was used as a solvent to prepare positive electrode slurry and negative electrode slurry. The positive electrode slurry was prepared at a solid-liquid ratio of 195 wt% (195 g of NMP: 100 g of positive electrode active material). The negative electrode slurry was prepared at a solid-liquid ratio of 60 wt% (60 g of NMP: 100 g of negative electrode active material). The formula of the positive electrode active material and the negative electrode active material is shown in Table 1.

[0079] Table 1 - Formulas of positive electrode active materials and negative electrode active materials

[0080]

[0081] The positive electrode slurry is applied to aluminum foil, and the negative electrode slurry is applied to electrolytic copper foil. After the solvent evaporates, the negative electrode and the positive electrode are pressed and cut into the required size. The positive and negative electrodes are stacked alternately, and the separator (Celgard) is sandwiched between them, and then placed in a container formed by the laminated film. The container is filled with electrolyte and sealed to form a battery. The size of the laminated lithium battery is 41mm×34mm×53mm.

[0082] Regarding the high rate charge and discharge test (e.g., charge-discharge test), the charge mode was constant current-constant voltage (CCCV) mode, the charge voltage was 4.2V, and the charge current was 5C. The discharge mode was constant current (CC) mode, the discharge voltage was 2.8V, and the discharge current was 5C. The charge-discharge test of the battery was performed at high temperature (55°C).

[0083] Table 2 shows the data of the designed experiment to illustrate some implementations of the electrolytic copper foil. The yield strength, core void volume, trough void volume, void volume and residual stress of the electrolytic copper foil are listed in the table. The charge-discharge cycle life of the stacked batteries prepared using the electrolytic copper foil is also listed in the table. Five experimental groups (E.1 to E.5) and four control groups (C.1 to C.4) are listed in sequence from left to right in the table. Compared with the charge-discharge cycles of the control groups C.1 to C.4 (less than about 900), the experimental groups E.1 to E.5 show excellent battery characteristics, as shown by the charge-discharge cycles (between 900 and 1200). The experimental data show that the high number of cycles obtained by E.1 to E.5 is consistent with the electrolytic copper foil having a resistance of 11kg / mm 2 Up to 45kg / mm 2The yield strength between the deposition surface and the roller surface is related to the ΔRS between the deposition surface and the roller surface being less than 95 MPa. The yield strength or ΔRS of the control groups C.1 to C.4 is one or both outside the range listed in E.1 to E.5.

[0084] Table 2 also shows the effect of void volume. In addition, the data shows the effect of void volume. For example, when the core void volume of the deposition surface is too low or too high, such as below about 0.14 (C.1 and C.2), or above about 1.15 (C.3 and C.4), the performance of the battery is not as good as when the core void volume of the deposition surface is between these values ​​(e.g., between 0.08 and 1.27, for E.1 to E.5).

[0085] When the void volume of the valleys of the deposition surface is high, such as above about 0.15 (C.3 and C.4), the cell performance is not as good as when the void volume of the valleys of the deposition surface is low, such as below about 0.15 (E.1 to E.5).

[0086] Compared to the good performance of the batteries E.1 to E.5 when the void volume is within the controlled range between about 0.09 and 1.48, the battery performance is poor when the void volume of the deposition surface is too low or too high, for example, below about 0.15 (C.1 and C.2), or above about 1.3 (C.3 and C.4).

[0087] Table 2

[0088]

[0089]

[0090] 3. Test Methods

[0091] Yield strength (0.5% EUL)

[0092] The yield strength values ​​in Table 2 are obtained from the examples and comparative examples by the method of IPC-TM-650 2.4.18. The electrolytic copper foil of each example and comparative example was cut into a size of 100 mm × 12.7 mm (length × width) to obtain a specimen, and the specimen was measured at room temperature (about 25°C) using an AG-I type testing machine produced by Shimadzu Corporation with a chuck distance of 50 mm and a crosshead speed of 50 mm / min. The measurement results were recorded after the applied force exceeded 0.075 kg. The yield strength (0.5% EUL) is obtained by drawing a straight line parallel to the Y-axis (stress) at the point where the strain is 0.5% (∈=0.005) in the curve of the relationship between strain and stress, which is consistent with the previous description of the yield strength (0.5% EUL). Figure 4 The narrative is similar.

[0093] Residual stress

[0094] The residual stress values ​​in Table 2 were obtained from the Examples and Comparative Examples using an X-ray Empyrean system manufactured by Panalytical as the measuring instrument. The X-ray tube was copper (wavelength = ), tube voltage was 45 kV, tube current was 20 mA. The examples and comparative examples were measured on an Empyrean system with a low grazing angle, using an X-ray mixing mirror in the incident beam, a 0.27 parallel plate collimator and a proportional counter in the diffracted beam.

[0095] Volume parameters

[0096] The void volume (Vv) values ​​in Table 2 are obtained from the examples and comparative examples according to the steps of ISO 25178-2 (2012). Surface texture analysis was performed from images taken from a laser microscope. The laser microscope was a LEXTOLS5000-SAF manufactured by Olympus, and the images were taken when the air temperature was 24±3°C and the relative humidity was 63±3%. The filter setting was set to unfiltered. The light source was a light source with a wavelength of 405nm. The objective lens was a 100x magnification (MPLAPON-100xLEXT). The optical zoom was set to 1.0x. The image area was set to 129μmx 129μm. The resolution was set to 1024 pixels x 1024 pixels. The condition was set to automatic tilt removal.

[0097] The core void volume is calculated with a loading rate of 10% for p and 80% for q, the valley void volume is calculated with a loading rate of 80%, and the void volume is calculated with a loading rate of 10%. The unit of void volume is μm 3 / μm 2 .

[0098] As used herein, the terms "comprising" or "comprise" are intended to be essential to the claimed invention, methods, and respective components thereof, but allow for the inclusion of unspecified elements, whether essential or not.

[0099] As used in this specification and claims, the singular forms "a", "an", and "the" are intended to include the plural forms unless the context clearly indicates otherwise. Thus, for example, reference to "the method" includes one or more methods, and / or steps of the type described herein and / or as will be apparent to one skilled in the art after reading this disclosure and the like. Similarly, the word "or" is intended to include "and" unless the context clearly indicates otherwise.

[0100] Except in the operating examples or otherwise indicated, in all cases, the numbers used herein to express the quantities of ingredients or reaction conditions should be understood to be modified by the term "about". The term "about" can mean ±5% (e.g., ±4%, ±3%, ±2%, ±1%) of the stated value.

[0101] When a numerical range is provided, it is intended to be between and including the upper and lower limits of the range disclosed herein.

[0102] Unless otherwise defined herein, scientific and technical terms used in conjunction with this application shall have the same meaning as commonly understood by those skilled in the art to which the invention belongs. In addition, unless otherwise required by context, singular terms shall include pluralities and plural terms shall include the singular.

[0103] It should be understood that the present invention is not limited to the specific methods, protocols and reactants described herein, and thus they may vary. The purpose of the terms used herein is only to describe specific implementations and is not intended to limit the scope of the present invention, which is limited only by the claims.

[0104] For the purpose of description and disclosure, any patents, patent applications and publications that include ASTM, JIS methods disclosed herein are expressly incorporated herein, for example, the methods described in the publications can be used in conjunction with the present invention. These publications are provided only because their disclosure precedes the filing date of the present invention. Nothing in this regard should be construed as an admission that the inventors are not entitled to antedate such disclosures by virtue of prior invention or for any other reason. Statements about dates or statements about the contents of these documents are based on information obtained by the applicant and are not to be construed as an admission that the dates or contents of these documents are correct.

Claims

1. An electrolytic copper foil, comprising: Roller surface; as well as a deposition surface opposite to the roller surface; wherein the roller surface and the deposition surface each have residual stress, wherein the residual stress difference between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 to 95 MPa; and The yield strength of the electrolytic copper foil is 11 kg / mm 2 Up to 45kg / mm 2 within the range of The void volume value between the deposition surface and the roller surface of the electrolytic copper foil is 0.17 μm. 3 / μm 2 To 1.11μm 3 / μm 2 The core void volume value is 0.14 μm 3 / μm 2 Up to 1.15μm 3 / μm 2 The maximum void volume value of the trough is 0.15 μm 3 / μm 2 .

2. The electrolytic copper foil according to claim 1, characterized in that: The yield strength of the electrolytic copper foil is 16kg / mm 2 Up to 36kg / mm 2 within the range.

3. The electrolytic copper foil according to claim 1, characterized in that: The residual stress difference between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 to 85 MPa.

4. The electrolytic copper foil according to claim 1, characterized in that: The residual stress difference between the roller surface and the deposition surface of the electrolytic copper foil is in the range of 7.4 to 81 MPa.

5. The electrolytic copper foil according to claim 1, characterized in that: The residual stress on the deposition surface of the electrolytic copper foil is in the range of -40 MPa to 100 MPa.

6. The electrolytic copper foil according to claim 1, characterized in that: The residual stress on the roller surface of the electrolytic copper foil is in the range of -47 MPa to 42 MPa.

7. The electrolytic copper foil according to claim 1, characterized in that: The thickness of the electrolytic copper foil is 3 μm to 20 μm. 8 . A negative electrode current collector comprising the electrolytic copper foil according to claim 1 . 9 . A negative electrode, comprising the negative electrode current collector according to claim 8 , and further comprising a negative electrode active material coated on the negative electrode current collector. 10 . A lithium ion secondary battery comprising the negative electrode according to claim 9 .

11. The lithium ion secondary battery according to claim 10, having a charge-discharge cycle life of at least 900 times.

12. A device comprising the lithium ion secondary battery according to claim 11.